Understanding Leadership and its Various Dimensions: A Mini-Review - Juneja, Jatinder Kaur (Innovare Journal of Education, 2022)
An important function of directing, leadership plays an important function in influencing behaviour and guiding it into achievement of organizational goals. Leaders are born and leadership skills can be learnt. Leaders are a key human resource in any organisation. The article covers all necessary ele of life.ments of leadership and its importance in every aspect